INTERPRETASI KONTEKSTUAL DALAM MEMAHAMI HADIS PENETAPAN AWAL BULAN QAMARIAH - as-Siddiq, Hasbi; Kurniati; Marilang (UIN ALAUDDIN MAKASSAR, 2025)
The purpose of writing this journal is to explain how contextual interpretation in understanding the hadith of determining the beginning of the Qamariah month. The absence of clear evidence that details the time limits, age or duration of a month, often causes differences in the implementation of the beginning of the fast of Ramadan, Eid al-Fitr, Arafah fasting and Eid al-Adha in Indonesia. This type of research is qualitative descriptive research with a library research method, namely research by collecting data from books, journals, and other data that are related to the discussion theme. The results of this study are the use of contextual interpretation methods in understanding the evidence in the present day needs to be massively implemented by considering the context that surrounds or is related to the text, both in terms of history and socio-cultural aspects, then connected to the current context through a holistic, multidisciplinary approach, ushul fiqh or an approach related to contemporary science. As for efforts to contextualize the understanding of the hadiths regarding the determination of the beginning of the lunar month, it is necessary to pay attention to the context of the past (the time of the Prophet Muhammad) and the current context.